The Correspondence of Sargon II. Part I: Letters from Assyria and the West - Parpola, Simo (1987)
Published by the Neo-Assyrian Text Corpus Project of the Academy of Finland in co-operation with Deutsche Orient-Gesellschaft. Editorial Committee: Karlheinz Deller, Frederick Mario Fales, Simo Parpola, Nicholas Postgate; = SAA I [contains 265 letters in new transcriptions and translations with glossary, indices and copies of collated passages].